A legal study of Child Act 2001 in dealing with children beyond control in Malaysia with reference to the position in Australia / Zalina Mohammad - Mohammad, Zalina (2017)
The aim of this study is to propose a legal obligation of parents to report cases on children beyond control. This situation happens when a parent fails to control the behavior of the child and the child gets involved in unhealthy activities. The researcher believes that it is necessary to prevent children beyond control at the parent stage, because parents are the closest and able to understand the situation of a child the most. The Increasing social problems among teenagers have become a hot issue and a major cause why the duty to report the case children beyond control is needed. In addition, the study also found that parents are the primary causes of this problem, as well peers influence and also other factors such as the influence of media and the impact of globalization on a country. Although so far no country has implemented the provision of mandatory reporting of children beyond control, the researcher has compared this issue with Australia as this country has a mechanism that is good in the out-of-home system, which is better than Malaysia in terms of implementation and provides a good and effective recovery programs for children. Finally, with this allocation the researcher believes it could help authorities to take an early action in helping a parent in rehabilitating their children. Last but not least, a proposal to impose and control the social problems in the country are explained in detail.